PRAKTEK TEORI AGENSI PADA ENTITAS PUBLIK DAN NON PUBLIK - Arifah, Dista Amalia (PRESTASI, 2012)
Game theory is the beginning of agency theory, game theory tries to find form and predict conflict resolution between individuals who are rational, and it helps us understand how managers, investors and other parties affected can be rationally agreed with the economic consequences of financial reporting. Agency theory is a branch of game theory that studies the design of contracts to motivate a rational agent to act on behalf of principal when the agentâs interests would otherwise conflict with those of the principal. In Indonesia, entities are divided into two sectors: public sector entities and private sector entities, although they differ in the ownership of the company but they both have similar traits. Both entities are equally divided into two parties that have the greatest interest, called the agent and principals. Both parties are often involved in conflicts of interest (conflict of interest), giving rise to agency cost.Agency conflict that occurs often brought losses to many parties, not only the parties in conflict alone but, more broadly. Be a mechanism to resolve complex mechanism both internally and externally. Internal mechanism with the revamping of the entity itself with providing the motivation of managers and shareholders to behave in a manner that advance corporate objectives. While the external mechanism is by application of the rules of the Regulator, such as the obligation to implement the Corporate Governance in an entity.Keyword : teori agensi, agen, principal, entitas public, entitas swasta